Analisis Peningkatan Daya Minat Dan Motivasi Belajar Siswa Menggunakan Delta Multimedia Edutainment Sebagai Media Penunjang Pembelajaran - Dina Fitria Murad; Willy Johan Widjaja Saputra (KILAT, 2019)
Professor Toshiko Kinosita stated that Indonesia's human resources are still very weak to support industrial and economic development. The reason is because the government has never put education as the most important priority. Education is not placed as the most important priority because the people of Indonesia, ranging from the layman to politicians and government officials, are only pursuing money pursuits to enrich themselves and never think long. The opinion of the Japanese Waseda University Professor is very interesting to study considering that the Indonesian government is now starting to look at education as a long-term investment, after all this time education has been neglected. One indicator is that the MPR has agreed to prioritize the education budget of at least 20% of the APBN or APBD. This step is an initial awareness of the importance of education as a long-term investment. This study measures the extent to which the correlation and impact of the use of Information Technology in the teaching and learning process on student achievement in SMA Negeri 8 Tangerang. This research also modeled a learning media with Multimedia method which we named Delta Multimedia Edutainment (DME) which is a local web-based learning media school. The target to be achieved is an increase in interest and student achievement in SMA Negeri 8 Tangerang. The results of this study are useful for schools in improving school performance and maintaining the quality of graduates.